OPTIMAL CONTROL IN A DYNAMIC MODELS OF MONOPOLY - Y. Aganin (Вестник университета)
The article studies profit maximization in three dynamic models of monopoly. The first one describes the dynamics of production and capital-labor ratio with equilibrium price, the second - the same amounts with non-equilibrium price and finally the third one analyzes the external financing of capital expenditures and working capital.